2010
DOI: 10.1108/09615531011056818
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pressure field in time domain using nonlinear reduced frequency approach in unsteady transonic flows

Abstract: Purpose -The purpose of this paper is to discuss the capability of nonlinear frequency domain (NLFD) method in predicting surface pressure coefficient presented in the time domain in unsteady transonic flows. Design/methodology/approach -In this research, the solution and spatial operator are approximated by discrete form of Fourier transformation and resulting nonlinear equations are solved by use of pseudo-spectral approach. Considered transonic flows involve different flow pattern on the airfoil surfaces. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Two-phase flow status widely consists of the power, petroleum, chemical employment, aerospace, and the nuclear energy [1][2][3][4][5] fields. Therefore, the complex free interfacial motion analysis between two phases is significant.…”
Section: Introductionmentioning
confidence: 99%
“…Two-phase flow status widely consists of the power, petroleum, chemical employment, aerospace, and the nuclear energy [1][2][3][4][5] fields. Therefore, the complex free interfacial motion analysis between two phases is significant.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the URANS models, ZDES is more compatible with the experimental data, especially in the higher frequencies. Capability of nonlinear frequency domain (NLFD) method in predicting details of unsteady transonic flow-fields was investigated by Kharati Koopaee et al (2010). Results showed that NLFD method could predict reasonable pressure distribution in the time domain except in vicinity of moving shock positions.…”
Section: Introductionmentioning
confidence: 99%